Avaliação da qualidade do serviço de logística: um estudo de caso empírico do setor farmacêutico - Filho, Cid Gonçalves; Villela Júnior, José Ignácio; Souki, Gustavo Quiroga (Revista de Administração da UFSM, 2009)
The opening of markets caused a great change in customer-supplier relationships. Regarding to this new context, it is up to companies to implement strategies that consider this new reality and differentiate them from their competitors. In a view of the fact that it is necessary to attend to customer expectations at a cost which guarantees minimum profitability to a company, customer service management becomes an important variable in guaranteeing a company’s competitive advantage. In this situation, the issue, which is the object of this research, arises at this point: how to evaluate the logistic services quality provided by a pharmaceutical companies from the point of view of its retail customers? This research has been developed through a survey measuring a reliable scale of Logistics Service Quality in a pharmaceutical industry.